Investigating Inflation Dynamics in Sudan - Moriyama, Kenji (IMF Working Papers; Working Paper, 2008)
This paper investigates inflation dynamics in Sudan using three different approaches: the single equation model, the structural vector-auto regression model and a vector error correction model. This is the first study in a low-income and a post-conflict country that uses these three separate techniques to understand inflation dynamics. The use of these approaches is particularly useful to check the robustness of the estimated parameters in the model for a country with limited data coverage and possible structural breaks. The estimated results suggest that money supply growth and nominal exchange rate changes affect inflation with 18-24 months time lag.